Residências terapêuticas: experiência dos residentes de saúde mental do programa da universidade do estado da Bahia - DOI: http://dx.doi.org/10.5212/Emancipacao.v.9i1.107115 - Alves, Miriam Santos; Casais, Noêmia de Aragão; Santos, Josenaide Engrácia dos (Emancipação, 2009)
O presente artigo é produto da experiência dos residentes do Núcleo de Saúde Mental da Residência Multiprofi ssional em Saúde da Universidade do Estado da Bahia (UNEB), na Residência Terapêutica (RT) do distrito sanitário de Itapagipe, localizado em Salvador-Bahia. Essa experiência teve inicio com a inserção dos residentes no Centro de Atenção Psicossocial - CAPS II do referido distrito, que, no planejamento das ações desenvolvidas no território, priorizou a residência terapêutica como lugar para desenvolver cuidado, por considerá-la dispositivo com possibilidade de reinvenção do existir do sujeito na comunidade. A escuta, o vínculo, o corpo, a música e a rua foram os principais recursos utilizados no processo de aproximação entre os atores envolvidos. Apesar de enigmática, na medida em que suscitou vários problemas sem respostas, a experiência na RT mostrou-se um terreno fértil para promover a cidadania e autonomia. Foi também reveladora, porque sinalizou possibilidades de reinvenção da vida, considerando todas as controvérsias da estratégia utilizada. Palavras-chave: Residência terapêutica. Saúde mental. <span style="font-size: 8pt; color: black; font-family: ";Helvetica";,";sans-serif";; mso-fareast-font-family: ’Times New Roman’; mso-themecolor: text1; mso-fareast-language: PT-BR; mso-ansi-language: EN-US;" lang="EN-US">Cuidado. <span style="font-size: 8pt; color: black; font-family: ";Helvetica";,";sans-serif";; mso-fareast-font-family: ’Times New Roman’; mso-themecolor: text1; mso-fareast-language: PT-BR; mso-ansi-language: EN-US;" lang="EN-US"> <span style="font-size: 8pt; color: black; font-family: ";Helvetica";,";sans-serif";; mso-fareast-font-family: ’Times New Roman’; mso-themecolor: text1; mso-fareast-language: PT-BR; mso-ansi-language: EN-US;" lang="EN-US">Abstract: The present paper is the outcome of the experience of residents of the multi professional residency program from the Mental Health Nucleus at the University of the State of Bahia (UNEB), specifi cally in the residency program in therapeutics, implemented in the health district of Itapagipe, Salvador, Bahia. The experience began at the Center for Psychosocial Healthcare (CAPS II) in the aforementioned district, which, in planning the actions to be developed, gave priority to the use of the residential program as a means of developing a strategy of care, since it was considered that an initiative of this type would successfully redefi ne the existence of the individual in the community. The main resources used in the process of approximating the actors involved included listening, bonding, and the use of body language, music and the streets. The experience gained from the residency program in therapeutics confi rmed that the initiative represents fertile ground for promoting citizenship and autonomy; however, the issue remains controversial in that various questions have been raised to which at present there are no answers. On the other hand, the experience is also revealing, since it constitutes a potential for reinventing the life of the individual while considering all the controversies raised during this strategy. <span style="font-size: 8pt; color: black; font-family: ";Helvetica";,";sans-serif";; mso-fareast-font-family: ’Times New Roman’; mso-themecolor: text1; mso-fareast-language: PT-BR; mso-ansi-language: EN-US;" lang="EN-US">Keywords<span style="font-size: 8pt; color: black; font-family: ";Helvetica";,";sans-serif";; mso-fareast-font-family: ’Times New Roman’; mso-themecolor: text1; mso-fareast-language: PT-BR; mso-ansi-language: EN-US;" lang="EN-US">: Residential therapeutics. Mental health. Care. <!– /* Font Definitions */ @font-face font-family:"Cambria Math"; panose-1:2 4 5 3 5 4 6 3 2 4; mso-font-charset:0; mso-generic-font-family:roman; mso-font-pitch:variable; mso-font-signature:-1610611985 1107304683 0 0 159 0; @font-face font-family:Calibri; panose-1:2 15 5 2 2 2 4 3 2 4; mso-font-charset:0; mso-generic-font-family:swiss; mso-font-pitch:variable; mso-font-signature:-1610611985 1073750139 0 0 159 0; /* Style Definitions */ p.MsoNormal, li.MsoNormal, div.MsoNormal mso-style-unhide:no; mso-style-qformat:yes; mso-style-parent:""; margin-top:0cm; margin-right:.85pt; margin-bottom:0cm; margin-left:0cm; margin-bottom:.0001pt; line-height:120%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US; .MsoChpDefault mso-style-type:export-only; mso-default-props:yes; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:Calibri; mso-fareast-theme-font:minor-latin; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; mso-bidi-font-family:"Times New Roman"; mso-bidi-theme-font:minor-bidi; mso-fareast-language:EN-US; .MsoPapDefault mso-style-type:export-only; margin-right:.85pt; line-height:120%; @page Section1 size:595.3pt 841.9pt; margin:70.85pt 3.0cm 70.85pt 3.0cm; mso-header-margin:35.4pt; mso-footer-margin:35.4pt; mso-paper-source:0; div.Section1 page:Section1; –><!–[if gte mso 10]> <mce:style><! /* Style Definitions */ table.MsoNormalTable mso-style-name:"Tabela normal"; mso-tstyle-rowband-size:0; mso-tstyle-colband-size:0; mso-style-noshow:yes; mso-style-priority:99; mso-style-qformat:yes; mso-style-parent:""; mso-padding-alt:0cm 5.4pt 0cm 5.4pt; mso-para-margin-top:0cm; mso-para-margin-right:.85pt; mso-para-margin-bottom:0cm; mso-para-margin-left:0cm; mso-para-margin-bottom:.0001pt; line-height:120%; mso-pagination:widow-orphan; font-size:11.0pt; font-family:"Calibri","sans-serif"; mso-ascii-font-family:Calibri; mso-ascii-theme-font:minor-latin; mso-fareast-font-family:"Times New Roman"; mso-fareast-theme-font:minor-fareast; mso-hansi-font-family:Calibri; mso-hansi-theme-font:minor-latin; > <! [endif] > O presente artigo é produto da experiência dos residentes do Núcleo de Saúde Mental da Residência Multiprofi ssional em Saúde da Universidade do Estado da Bahia (UNEB), na Residência Terapêutica (RT) do distrito sanitário de Itapagipe, localizado em Salvador-Bahia. Essa experiência teve inicio com a inserção dos residentes no Centro de Atenção Psicossocial - CAPS II do referido distrito, que, no planejamento das ações desenvolvidas no território, priorizou a residência terapêutica como lugar para desenvolver cuidado, por considerá-la dispositivo com possibilidade de reinvenção do existir do sujeito na comunidade. A escuta, o vínculo, o corpo, a música e a rua foram os principais recursos utilizados no processo de aproximação entre os atores envolvidos. Apesar de enigmática, na medida em que suscitou vários problemas sem respostas, a experiência na RT mostrou-se um terreno fértil para promover a cidadania e autonomia. Foi também reveladora, porque sinalizou possibilidades de reinvenção da vida, considerando todas as controvérsias da estratégia utilizada. Palavras-chave: Residência terapêutica. Saúde mental. Cuidado. The present paper is the outcome of the experience of residents of the multi professional residency program from the Mental Health Nucleus at the University of the State of Bahia (UNEB), specifi cally in the residency program in therapeutics, implemented in the health district of Itapagipe, Salvador, Bahia. The experience began at the Center for Psychosocial Healthcare (CAPS II) in the aforementioned district, which, in planning the actions to be developed, gave priority to the use of the residential program as a means of developing a strategy of care, since it was considered that an initiative of this type would successfully redefi ne the existence of the individual in the community. The main resources used in the process of approximating the actors involved included listening, bonding, and the use of body language, music and the streets. The experience gained from the residency program in therapeutics confi rmed that the initiative represents fertile ground for promoting citizenship and autonomy; however, the issue remains controversial in that various questions have been raised to which at present there are no answers. On the other hand, the experience is also revealing, since it constitutes a potential for reinventing the life of the individual while considering all the controversies raised during this strategy. Keywords: Residential therapeutics. Mental health. Care.<–>